Analyzing gut microbiota composition in individual Anopheles mosquitoes after experimental treatment - Aminata Fofana (Elsevier, 2021)
Summary: The microbiota of Anopheles mosquitoes influences malaria transmission. Antibiotics ingested during a blood meal impact the mosquito microbiome and malaria transmission, with substantial differences between drugs. Here, we assessed if amoxicillin affects the gut mosquito microbiota. We collected Anopheles larvae in Burkina Faso, kept them in semi-field conditions, and offered a blood meal to adult females. We tested the impact of blood supplementation with two alternative amoxicillin preparations on microbiota composition, determined by high-throughput sequencing in individual gut samples. Our analysis detected four major genera, Elizabethkingia, Wigglesworthia, Asaia, and Serratia. The antibiotic treatment significantly affected overall microbiota composition, with a specific decrease in the relative abundance of Elizabethkingia and Asaia during blood digestion. Besides its interest on the influence of amoxicillin on the mosquito microbiota, our study proposes a thorough approach to report negative-control data of high-throughput sequencing studies on samples with a reduced microbial load.